The Impact of Using E-Government on Employee Productivity and Performance in DP3APPKB Surabaya City - Lukman, Yenny; Amin, Faris Muslihul; Khalid; Gunawan, Ivan (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
This article analyzes the effect of E-Government on employee productivity and performance at the Surabaya City Office of Women's Empowerment, Child Protection, and Family Planning (DP3APPKB). In the growing digital era, the implementation of E-Government is important to improve the efficiency of public services. This study involved 30 employees and used quantitative analysis with linear regression. The results show that E-Government contributes significantly to productivity with a value of 48.4 persen, but its impact on employee performance is only 20.4 persen. This finding indicates that there are other factors that affect performance. This article recommends improving infrastructure and digital literacy among employees to maximize the benefits of E-Government, so that it can serve as a guide for other government agencies in more effective implementation.